2006
DOI: 10.1007/s00424-006-0164-4
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interindividual variation in gene expression in human adipose tissue

Abstract: Adipose tissue is a highly plastic tissue with an important endocrine and metabolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 64 publications
2
31
0
Order By: Relevance
“…Previous studies reported similar levels of FABP4 mRNA in human VAT and SAT (6,44,45). Our findings that FABP4 protein is higher in both human VAT and mouse intra-abdominal fat suggest that FABP4 may also be regulated posttranscriptionally.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies reported similar levels of FABP4 mRNA in human VAT and SAT (6,44,45). Our findings that FABP4 protein is higher in both human VAT and mouse intra-abdominal fat suggest that FABP4 may also be regulated posttranscriptionally.…”
Section: Discussionsupporting
confidence: 79%
“…In our hands, in vivo hASC-mediated calvarial repair does indeed vary between hASC source. Differences in age of the patient, gender, anatomic site of ASC derivation, passage number, and freeze-thaw conditions have all been shown to create disparity in the osteogenic in vitro differentiation of ASCs [35,[57][58][59][60]. We have attempted to counteract this apparent heterogeneity by selecting similar patients for hASC derivation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study may serve either as impetus toward the betterment of procedures of cryostorage of hASCs or alternatively toward the avoidance of freezing hASCs in general. Previous observations from our laboratory and others have found that the osteo-and adipogenic differentiation of ASCs does vary based on patient, age, gender, and anatomic site of derivation [51][52][53][54][55]. Thus, to minimize potential heterogeneity, all hASCs were consistently derived from young, female patients from the flank and thigh regions only.…”
Section: Discussionmentioning
confidence: 99%